Neuroprotective effect of intravenous lipid emulsion after bupivacaine-induced cardiac toxicity - Mevlüt Doğukan; Nezir Yılmaz; Ahmet Türk; Fadime Tosun; Mehmet Duran; Zeliha Bozkurt (Saudi Journal of Anaesthesia, 2025)
Background: This study aimed to investigate the protective effects of intravenous lipid emulsion (ILE) against bupivacaine-induced cardiac toxicity, using histopathological analyses. Methods: Twenty-eight adult male Wistar-Albino rats were divided into four groups: Sham (Group A), ILE (Group B), Bupivacaine (Group C), and Bupivacaine + ILE (Group D). Neurotoxicity was induced in Groups C and D with continuous bupivacaine infusion. ILE was administered to Groups B and D. Histological examination of brain tissues, and apoptotic index were evaluated. Results: The apoptotic index was significantly higher in Group C, but ILE administration in Group D markedly decreased these parameters (P < 0.05). Histopathological analysis revealed that ILE reduced edema and neuronal degeneration in Group D. Conclusion: ILE demonstrated a neuroprotective effect against bupivacaine-induced cardiac toxicity by improving hemodynamic stability and reducing cellular damage. This suggests a potential therapeutic role of ILE in managing local anesthetic systemic toxicity.